UJI AKTIVITAS ANTIBAKTERI PADA ALGA LAUT Gracilaria edulis (S.G. GMELIN) P.C SILVA DARI PERAIRAN PULAU NAIN KABUPATEN MINAHASA UTARA - Singkoh, Marina (CHEMISTRY PROGRESS, 2010)
ABSTRACTLengkong, H dan M. F. O. Singkoh. 2010. Antibacteria effect on sea algae Gracilaria edulis (S.G. Gmelin) P.C Silva from Nain island sea, North Minahasa regency.Marine algae possess the biggest part of marine plants in which they could morphologically be classified into thallus plants (Thallophyta) due to having no difference in sceletal structures, such as root, stem and leaf. Despite different shapes, the algae body structure consists only of stem called thallus. Algae are non-vascular plants which photosyntesize using chlorophyll a and have simple reproductive structures. They are unicellular and multicellular. This study was aimed at determining antibacterial activities of Gracilaria edulis. The study was carried out in approximately 6 months, January to June. Species Gracilaria edulis were collected from the coastal waters of Nain Island, North Minahasa Regency, North Sulawesi. These were studied in laboratory. The antibacterial test showed that the test solution of G. edulis an antibacterial activity on 5 test bacteria..Keywords: antibacteria, algae, Gracilaria edulis